2017
DOI: 10.1177/0894486517722887
|View full text |Cite
|
Sign up to set email alerts
|

Blame You, Blame Me: Exploring Attribution Differences and Impact in Family and Nonfamily Firms

Abstract: We explore how publicly listed family and nonfamily firms engage in self-serving attributions in their annual financial reports. We empirically examine how both types of firms emphasize internal attributions for good firm performance (internal-positive attributions) and external attributions for poor firm performance (external-negative attributions). We find that family firms make more external-negative attributions and that the stock market reacts more negatively to external-negative attributions made by fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 117 publications
0
14
0
Order By: Relevance
“…However, we must be cautious about assigning causality, given our available data and the nature of micro-firms. For instance, we note prior research has found small/family firms ‘blame’ external factors (like regulation) for poor performance, thereby suggesting poor performance drives onerous regulatory perceptions (Gomez-Mejia et al., 2001; Hienerth and Kessler, 2006; Jayamohan et al., 2017). However, while this cannot be discounted, by exploring the Perceived-Value and Perceived-Burden independently, we gain a more nuanced understanding of regulation.…”
Section: Wider Discussionmentioning
confidence: 81%
“…However, we must be cautious about assigning causality, given our available data and the nature of micro-firms. For instance, we note prior research has found small/family firms ‘blame’ external factors (like regulation) for poor performance, thereby suggesting poor performance drives onerous regulatory perceptions (Gomez-Mejia et al., 2001; Hienerth and Kessler, 2006; Jayamohan et al., 2017). However, while this cannot be discounted, by exploring the Perceived-Value and Perceived-Burden independently, we gain a more nuanced understanding of regulation.…”
Section: Wider Discussionmentioning
confidence: 81%
“…That self-interest orientation leads them to avoid risky projects or pursue unethical strategic activities, such as earnings management (Jiraporn et al 2008 ) or tax avoidance (Desai and Dharmapala 2006 ). In a broader perspective, managers hire public relations (Jayamohan et al 2017 ; Westphal and Graebner 2010 ) or decrease financial readability (Leung et al 2015 ) to hide important information about their lack of performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Given this assumed impression management, research suggests that managers will find reasoning to justify their failure (Jayamohan et al 2017 ; Zerfass 2008 ). In particular, managers use corporate financial reports to convey their reasoning for the declining performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…We also contribute to signaling theory in general and family firm signaling in particular by studying negative CSR news, which can be seen as an unintentional signal (i.e., a signal that signalers emit without being aware that they are signaling [Spence, 2002]), as well as recessions as a signaling environment-both of which relate to understudied areas in the signaling research field (Connelly et al, 2011). Second, we contribute to the research on family firms by investigating the consequences of CSR news, especially its effect on the stock market (Jayamohan et al, 2017). Specifically, we show that in general, positive CSR news about family firms is perceived positively and negative CSR news is perceived negatively by outside investors-a finding that also carries important practical implications.…”
Section: Introductionmentioning
confidence: 99%